The Effect of Workplace Stretching Exercise (WSE) Intervention on Musculoskeletal Complaints Among Nursing Students in Clinical Practice - Weni Widya Shari; Ritta Farma (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2024)
Background: Musculoskeletal complaints are a common discomfort experienced by nursing students during clinical practice in hospitals. This occurs because they do not pay attention to important factors that pose risks, particularly related to improper patient handling. One intervention used to address these complaints is Workplace Stretching Exercise (WSE). WSE is a series of muscle-stretching exercises designed to relax and increase the flexibility of muscles that are considered problematic. Objectives: To determine the effect of WSE on musculoskeletal complaints among nursing students during clinical practice in hospitals. Methods: This research is a pre-experimental study with a two-group pre-test and post-test design. The sample consists of 26 individuals in both the intervention and control groups, selected using purposive sampling. The questionnaire used is the Nordic Body Map (NBM) to detect musculoskeletal complaints. Results: Statistical test results using the Wilcoxon test showed p = 0.000 (α = 0.05), indicating that WSE has an effect on musculoskeletal complaints among nursing students during clinical practice in hospitals. Conclusion: WSE should be routinely performed by nursing students during clinical practice to address musculoskeletal complaints.